2021
DOI: 10.1108/jec-04-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Innovation capabilities of women enterprise in informal settings

Abstract: Purpose This paper aims to explore how women entrepreneurs in informal settings, especially in the fishing sub-sector in rural communities, relate to different dimensions of innovation. Specifically, this paper examines how women entrepreneurs engage in process, managerial and technological innovations. This paper also examines how they fund their business, develop their products across the value chain innovatively and how it influences their business output and welfare. Design/methodology/approach A face-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A broad review of the existing literature allows the following groups of possible IC determinants to be indicated: (1) the personal characteristics of a micro-enterprise's owner or manager, (2) organisational characteristics and (3) external environmental characteristics. [33] Innovation capability relates to the adoption and implementation of useful ideas.…”
Section: Innovation Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A broad review of the existing literature allows the following groups of possible IC determinants to be indicated: (1) the personal characteristics of a micro-enterprise's owner or manager, (2) organisational characteristics and (3) external environmental characteristics. [33] Innovation capability relates to the adoption and implementation of useful ideas.…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…The search to find an answer to the question of how to build an enterprise's innovation potential is still ongoing [1][2][3]. This is especially important in the context of many opinions that a firm's success often depends on its ability to innovate [4].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that education level and learning skills are significant predictors of process innovation capacities among women-owned businesses in informal settings. Whereas, education level, years of experience and learning capabilities are significant predictors of technical innovation (Adeosun et al , 2020).…”
Section: Introductionmentioning
confidence: 99%